Marijuana buyers in the United States, 2010–2014. (1st February 2018) - Azofeifa, Alejandro; Sherman, Laura J.; Mattson, Margaret E.; Pacula, Rosalie L.
Highlights: Over half of all U.S. marijuana users reported buying marijuana in the past year. 1.8 million underage individuals reported buying marijuana in the past year. Most past year marijuana buyers were frequent users and had marijuana dependence. Data showed differences of proportion of marijuana buyers by state of residence. Studies are needed to monitor the consumer base, especially among underage individuals. Abstract: Background: Obtaining or purchasing marijuana in the U.S. can be done only in certain states via a lawful market for medical or non-medical (recreational) purposes, or via an unlawful market ("black market") by home cultivation and unlicensed vendors and individuals. Given the evolving U.S. state marijuana legislation landscape, the objective of this study is to describe individuals who report buying marijuana in the past year by selected characteristics and U.S. geographical location. Methods: Using data from the 2010–2014 National Survey on Drug Use and Health (NSDUH), we conducted bivariate chi-square tests to examine sociodemographic and selected behavioral indicators associated with buying marijuana and analyzed these factors in a multivariable logistic regression model. NSDUH participants were the noninstitutionalized civilian population aged 12+ (approximately 62, 100 individuals per year) who reported using marijuana in the past year (approximately 12, 400 annual average). Results: A weighted estimate of approximately 18.5 million individuals aged 12+ reported buying marijuana in the past year (59% of marijuana users). Overall, buyers of marijuana were more likely to be male, report using marijuana for a greater number of days, and to meet the criteria for substance use disorder and marijuana dependence. Data showed differences of proportion of marijuana buyers by state of residence. Conclusions: Given recent changes in state laws and policies and the increased demand for marijuana products, continued monitoring of the U.S. marijuana market in coming years is important in order to understand consumption and buying patterns among at-risk segments of the population, especially youth.